Tumor-associated macrophages promote resistance of hepatocellular carcinoma cells against sorafenib by activating CXCR2 signaling - Hao-Chen Wang; Lin-Ya Haung; Chih-Jung Wang; Ying-Jui Chao; Ya-Chin Hou; Chia-Jui Yen; Yan-Shen Shan (Journal of Biomedical Science, 2022)
Abstract Background Sorafenib (SOR) is the first line treatment for advanced hepatocellular carcinoma (HCC), but resistance develops frequently. Tumor-associated macrophages (TAMs) have been reported to affect the progression of HCC. We therefore aimed to study the role of TAMs in promoting SOR resistance. Methods Immunofluorescence staining for the M2 marker CD204 and the cancer stem cell (CSC) markers CD44 and CD133 was performed in paired HCC and adjacent noncancerous tissues and HCC tissues stratified by response of SOR treatment. HCC/U937 coculture system and cytokines were used to induce M2 polarization for studying the effects of M2 TAMs on CSC properties and apoptotic death of HCC cells after SOR treatment. Results Higher expression of CD204, CD44, and CD133 was observed in patients with SOR nonresponse (SNR) than in those with SOR response (SR), suggesting that SNR is positively correlated to levels of CSCs and M2 TAMs. After coculture, M2 TAMs could increase the level of CSCs but decrease SOR-induced apoptosis. Incubation of HCC cells with coculture conditioned medium increased the formation of spheres that were resistant to SOR. Furthermore, CXCL1 and CXCL2 were found to be the potential paracrine factors released by M2 TAMs to upregulate SOR resistance in HCC cells. Treatment with CXCL1 and CXCL2 could increase HCC CSC activity but decrease SOR-induced apoptosis by affecting BCL-2 family gene expression. Using pharmacological inhibitors, CXCR2/ERK signaling was found to be critical to CXCL1- and CXCL2-mediated SOR resistance. Conclusion This study identified CXCL1, CXCL2, and their downstream CXCR2/ERK signaling as potential therapeutic targets to overcome SOR resistance in HCC.